Does local implantation of gentamicin impair renal function in patients undergoing surgery for chronic bone infection? - Muir, Ross; Birnie, Catherine; Hyder-Wilson, Robert; Ferguson, Jamie; McNally, Martin A. (International Journal of Research in Orthopaedics, 2021)
Background: The treatment of chronic bone infection often involves excision of dead bone and implantation of biomaterials which elute antibiotics. Gentamicin is a preferred drug for local delivery, but its systemic use carries a well-established risk of nephrotoxicity. We aim to establish the risk of acute kidney injury (AKI) with local delivery in a ceramic carrier. Methods: 163 patients with Cierny-Mader type 3 or 4 chronic osteomyelitis had a single-stage operation including filling of the osseous defect with a calcium sulphate-hydroxyapatite carrier containing gentamicin. Mean gentamicin dosing was 191.3 mg (maximum 525 mg). Glomerular filtration rate (GFR) was calculated pre-operatively and during the first seven days post-operatively. Renal impairment was graded using the chronic kidney disease (CKD) staging system, and AKI was assessed using the RIFLE criteria. Results: 155 cases had adequate data to allow calculation of pre- and post-operative GFR. 7 had pre-existing renal disease. 70 patients (45.2%) had a temporary GFR drop post-operatively, with the greatest decrease occurring at a mean of 3.06 days following surgery. Twenty cases had a >10% decline in GFR, but 12 resolved within 7 days. 7 patients transiently fell into the “Risk” category according to RIFLE criteria, but no patient had a change consistent with “Injury”, “Failure” or “Loss” of renal function and none had clinical signs of new acute renal impairment post-operatively. Conclusions: Renal function is not significantly affected by local implantation of gentamicin up to 525 mg. The presence of pre-existing renal disease is not a contraindication to local gentamicin therapy.